Bio-inspired route of metal nanoparticles synthesis and photocatalysts doping - Chelli, Venkatanarasimha Rao (My University, 2018)
The conventional methods of nanoparticles (NPs) synthesis are sonochemistry, laser ablation, co-precipitation, sol-gel procedures, solvothermal, chemical reduction, and photo-reduction. All these methods are chemical and energy intensive, hence, costly. Thus, a greener route of environmentally benign NPs synthesis has gained tremendous success in recent times. The bio-mediated methods are straightforward and eco-friendly and, the whole process can be carried out at room temperature and pressure. The intercellular synthesis of NPs using microbes often shows a lower synthesis rate as well as difficulty in size and shape control. Such problems can be overcome in many extents by extracting the bio-analytes in a suitable media from the living cells. After that, the particles are synthesized in this media. Faster kinetics and minimization of aggregation of particles are the main challenges of the bio- and bio-mediated processes.Sechium edule, fruits of a perennial climber, is rich in ascorbic acid (AA 294 mg/kg dry fruit). In the first part of this work, the bio-analytes were extracted in an aqueous media for the synthesis of AgNPs. The study emphasizes on the mechanism of formation of mono-crystalline AgNPs at different pH which in turn controls the kinetics and size of AgNPs. Thermodynamically facile Ag2O reduction at a higher pH (≥ 9) resulted in spherical particles of smaller sizes; however, the particles were laden with a trace of Ag2O at pH 12.5. A broad and bimodal distribution of AgNPs of different shapes and sizes were originated at a lower pH (3≤pH≤5) from Ag+ and Ag2O reductions where AA mostly exists as dehydro-AA. A single surface plasmon resonance peak at 425 nm exhibited a blue shift with the decrease in AgNPs size and increase in sphericity in the abundance of OH– ions. The hydrodynamic diameter of AgNPs was around 1.6 times greater than the dry particles from TEM micrograph at the natural pH (5.8) of the bio-extract. AgNPs were tested for the inactivation of Bacillus subtilis and Escherichia coli bacteria
Golder, Animes Kr.
Keywords: CHEMICAL ENGINEERING